Гнездовая жизнь обыкновенной пустельги (Falco tinnunculus tinnunculus L.) в низовьях реки Зарафшан - Сагитов, А.К.; Бакаев, С.Б. (Вестник зоологии, 1971)
The article deals with the dat a on nesting life of Falco tinnunculus tinnunculus L., time of their returning to the habitat, nest construction, mating, clutch, egg incubation, rearing of nestlings as well as with the data on nutrition of nestlings and adult birds.